Supercritical fluid extraction : principles and practice - McHugh, Mark A. (Butterworth-Heinemann series in chemical engineering., 1994)
Supercritical Fluid Extraction is a technique in which CO2 is used under extremely high pressure to separate solutions (e.g., removing caffeine from coffee). Separation is basic to all process industries and supercritical fluid extraction is a specific type, receiving a high level of attention. This book combines basic fundamentals with industrial applications. This second edition has been expanded and updated and includes new chapters on chromatography and food processing.